Adjusting for risk factors in mutual fund performance and performance persistence: Evidence from the Greek market during the debt crisis. Issue 4 (2nd October 2019) - Koutsokostas, Drosos; Papathanasiou, Spyros; Balios, Dimitris
Abstract : Purpose: The purpose of this paper is to examine the performance of Greek equity mutual funds and the persistence in annual performance for the period 2008-2017 by using a variety of performance models. Design/methodology/approach: Using all the available funds in operation and daily data, the authors apply single-index (Jensen, 1968 ) and multi-factor models (Fama and French, 1993 ; Carhart, 1997 ) to measure risk-adjusted returns. To assess performance persistence, a series of parametric (Bollen and Busse, 2005 ) and nonparametric tests (Malkiel, 1995 ; Brown and Goetzmann, 1995 ; Kahn and Rudd, 1995 ) is implemented. Findings: Results show that the Greek equity mutual funds perform, on average, worse than the market index, irrespective of the performance measure applied, and the estimations obtained by the models are similar. Few managers that followed large-cap strategies, pursued stocks with high book-to-market value ratio and eliminated their exposure to the momentum effect were able to add value to their portfolios. Furthermore, a winner-picking strategy based on sustained superior performers is questioned. However, assigning fund returns to the corresponding risk factors results in the partial disappearance of persistence in performance. Originality/value: The sample period includes the turbulent period, following the introduction of capital controls, which affected capital flows significantly. Moreover, the application of multiple performance measures enables us to investigate performance persistence in a wider spectrum.